2014
DOI: 10.1208/s12249-014-0206-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Pharmacokinetic Study of Mangiferin After Oral Administration of Pure Mangiferin and US Patented Polyherbal Formulation to Rats

Abstract: Abstract. The US patented polyherbal formulation for the prevention and management of type II diabetes and its vascular complications was used for the present study. The xanthone glycoside mangiferin is one of the major effector constituents in the Salacia species with potential anti-diabetic activity. The pharmacokinetic differences of mangiferin following oral administration of pure mangiferin and polyherbal formulation containing Salacia species were studied with approximately the same dose 30 mg/kg mangife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 23 publications
(21 reference statements)
0
13
0
Order By: Relevance
“…After oral administration, the mean t 1/2 of mangiferin in normal rats appeared to be significantly prolonged than that in the reported studies [13,19,21,22]. Furthermore, the mean (SD) t 1/2 of mangiferin in alloxan-induced rats was 8.34 (2.18) h with a 2.21-fold increase compared with that of STZ-induced rats [13].…”
Section: Doi: 101159/000493364mentioning
confidence: 52%
See 1 more Smart Citation
“…After oral administration, the mean t 1/2 of mangiferin in normal rats appeared to be significantly prolonged than that in the reported studies [13,19,21,22]. Furthermore, the mean (SD) t 1/2 of mangiferin in alloxan-induced rats was 8.34 (2.18) h with a 2.21-fold increase compared with that of STZ-induced rats [13].…”
Section: Doi: 101159/000493364mentioning
confidence: 52%
“…However, to date, pharmacokinetic data for mangiferin are mostly derived from healthy [19][20][21][22] and STZinduced diabetic rats after oral administration [13]. To the best of our knowledge, no investigation has been reported about the pharmacokinetics of mangiferin in alloxan-induced diabetic rats.…”
Section: Introductionmentioning
confidence: 99%
“…The point of maximum plasma concentration (38.64 ng/mL −1 ) was at approximately 1 h, and was surprisingly low considering the dose of 0.9 g. This outcome supports other published findings such as those reported by [ 89 , 91 ] in rats. Maximal plasma concentrations, both quantity and time, were enhanced when mangiferin was orally administered to rats as a polyherbal formulation, rather than as mangiferin alone [ 92 ]. Similarly, Ma et al, in a rat model, found that permeability and plasma concentrations were improved following administration of a phospholipid complex containing mangiferin, relative to administration of mangiferin alone [ 93 ].…”
Section: Bioavailability and Delivery Of Mangiferinmentioning
confidence: 99%
“…WinNonlin computer software (WinNonlin® 6.3, Phoenix™, USA) was used for the determination of the pharmacokinetic parameters C max (maximum drug concentration), T max (time to reach the maximum drug concentration) , t 1/2 (half-life) , K el (terminal elimination rate constant), AUC 0-24h (area under the plasma concentration-time curve) and AUC 0-∞ (area under the plasma concentration-time curve extrapolated to infinity to obtain last measurable plasma drug concentration). [21][22][23][24] All results are expressed as the arithmetic mean ± standard deviation. The statistical analysis, scientific graphing and data evaluation were performed using Excel-2007 (Microsoft, New York, USA).…”
Section: Discussionmentioning
confidence: 99%